The three battles of Wanat and other true stories - Bowden, Mark 1951- (Atlantic Monthly Press, 2016)
"In addition to three extraordinary pieces on war, this book includes Bowden's incisive sports writing, think pieces, and a selection of fascinating profiles--from a piece on the world's youngest and most baffling dictator, Kim Jong-un, to features on newspaper scion Arthur Sulzberger and The Wire creator, David Simon"--Back jacket flap.